The AI Revolution in Primary Care: Enhancing Diagnosis, Efficiency, and Patient Outcomes - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The AI Revolution in Primary Care: Enhancing Diagnosis, Efficiency, and Patient Outcomes Primary care, the bedrock of any robust healthcare system, is c...
Keywords: Diagnostics; Artificial Intelligence; Healthcare Innovation; Medical Ethics; Patient Care